2017
DOI: 10.33396/1728-0869-2017-6-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual Exposure Load of Formaldehyde and Adolescents’ Organism Sensibilization

Abstract: All environmental factors influence on the human directly or indirectly. The biggest influence has the outdoor air, which is one of the major health risk factors associated with the environment. The proportion of 9-18 % of the total hazard index of inhalation exposure belongs to formaldehyde, which has a general toxic, sensibilizing and allergic effect. The frequency of allergic rhinitis and asthma in children living in the industrial cities of Eastern Siberia is 28-36 %. The purpose of the study was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
0
5
0
4
Order By: Relevance
“…Formaldehyde in the atmospheric air of low-lying cities is a product of photo-oxidation of hydrocarbons produced as a result of incomplete fuel combustion, and a typical component of smog in low-lying cities. Owing to its high reactive chemical activity, formaldehyde is capable of changing the course and intensity of metabolic processes, causing damage to DNA and protein molecules in human cells [17], having mutagenic, carcinogenic, teratogenic, general toxic, sensitizing and allergenic effects [18]. It is revealed that the content of formaldehyde in the atmospheric air relates to the development frequency of the bronchial asthma [19].…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde in the atmospheric air of low-lying cities is a product of photo-oxidation of hydrocarbons produced as a result of incomplete fuel combustion, and a typical component of smog in low-lying cities. Owing to its high reactive chemical activity, formaldehyde is capable of changing the course and intensity of metabolic processes, causing damage to DNA and protein molecules in human cells [17], having mutagenic, carcinogenic, teratogenic, general toxic, sensitizing and allergenic effects [18]. It is revealed that the content of formaldehyde in the atmospheric air relates to the development frequency of the bronchial asthma [19].…”
Section: Introductionmentioning
confidence: 99%
“…Загрязнение воздушной среды играет значимую роль в формировании риска нарушения здоровья населения, а экополлютанты способны выступать в качестве аллергенов и сенсибилизирующих агентов и вызывать развитие аллергических заболеваний [3,4]. Доказано, что загрязнение воздуха формальдегидом, бенз(а)пиреном, фенолом, диоксидом азота оказывает влияние на функционирование иммунной системы, вызывая увеличе-ние синтеза провоспалительных цитокинов, снижение содержания IgA, повышение уровней специфических аутоантител, ингибирование гибели клеток по типу апоптоза и активации путем некроза, а также ассоциировано с аллергопатологией у взрослых и детей [5][6][7][8].…”
unclassified
“…Для оценки влияния экспозиции химическими соединениями родительского поколения в предгестационный период были использованы данные о профессиональных маршрутах работников и содержании загрязнителей в воздухе рабочей зоны. Информация о содержании химических соединений в воздушной среде была получена из информационных баз Роспотребнадзора Иркутской области, Росгидромета, а также материалов исследований, которые проведены сотрудниками ФГБНУ ВСИМЭИ и представлены в работах [5,9,22,23]. В лонгитюдных исследованиях Н.М.…”
unclassified
See 2 more Smart Citations